Analisis Peran Sektor Pertambangan dalam Pembangunan Regional Berkelanjutan di Provinsi Sumatera Selatan dengan Menerapkan Pendekatan Analisis Model Input-Ouput - Rizky Syaputra; Andyono Broto Santoso; Nofrohu Retongga; Lia Alfianita; Nur Widi Astanto Agus Tri Heri; Frida Rosidatul Mu’awanah (Jurnal Teknologi, Fakultas Teknologi Industri, Institut Sains & Teknologi AKPRIND Yogyakarta, 2023)
Sustainable regional development aims to increase regional competitiveness, increase economic growth, reduce regional inequality, and improve people's lives. South Sumatra Province is one of the provinces in Indonesia with excellent coal mining potential and can encourage sustainable regional development. The development of a sector cannot be separated from the support of other sectors, so optimizing the allocation of routine and development budgets into the economic sector is essential. For this reason, it is necessary to calculate the output impact analysis and analysis of the impact of gross value added on government expenditure using the input-output model. The calculation through this input-output model shows how much influence the increase or decrease in output and gross value added has on government expenditure. The role of the coal mining sector with other sectors and the condition of its existence in the economy need to be studied using the input-output table to determine the part of the mining sector in the regional economy. It can be concluded that the coal mining sector is still one of the leading sectors in economic growth in South Sumatra Province.